Analytical and experimental model of an energy harvesting system - Shishkovski, Dejan; Pecioski, Damjan; Ignjatovska, Anastasija; Domazetovska, Simona; Anachkova, Maja (IEEE, 2023)
The conversion of energy in real processes is not ideal and as a result, there is always a certain percentage of wasted energy. This energy, such as mechanical energy from vibrations, could be reused by employing energy-harvesting systems. In this paper, a cantilever beam energy harvesting system for low-power consumption devices using piezoelectric materials has been developed. This system uses the byproduct of mechanical vibrations generated from a rotating machine. Piezoelectric materials’ characteristic to generate voltage as a result of being deformed, combined with their high robustness and efficiency makes them an ideal energy-harvesting tool. A mathematical model of these materials along with the whole system has been developed in Matlab and a simulation of the model using a Final Element Method (FEM) software has been created. Thereafter, an experimental model has been created in order to test and validate the obtained results from the simulations. A higher voltage output of the piezoelectric materials could be achieved by increasing the strain of the material. Therefore, maximal strain of the beam for the given frequency range of the vibration source would have to be achieved. Using the Euler Bernoulli method, the beam dimensions have been calculated so that its’ natural frequency matches the operating machine frequency. Finally, a consumer has been connected in order to calculate the power output of the designed system, so its practical application could be tested.
Keywords: energy harvesting from vibrations, piezoelectric transducers, natural frequency power generation